Structure of a self-splicing group II intron catalytic effector domain 5: Parallels with spliceosomal U6 RNA - SEETHARAMAN, MAHADEVAN (Copyright 2006 by RNA Society, 2006)
Domain 5 (D5) is absolutely required for all catalytic functions of group II introns. Here we describe the solution NMR structure, electrostatic calculations, and detailed magnesium ion-binding surface of D5 RNA from the Pylaiella littoralis large ribosomal RNA intron (D5-PL). The overall structure consists of a hairpin capped by a GNRA tetraloop. The stem is divided into lower and upper helices of 8 and 5 bp, respectively, separated by an internal bulge. The D5-PL internal bulge nucleotides stack into the helical junction, resulting in a coupling between the bulge A25 and the closing base pair (G8–C27) of the lower helix. Comparison of the D5-PL structure to previously reported related structures indicates that our structure is most similar, in the helical regions, to the crystal structure of D5 from yeast Ai5γ (D5-Ai5γ) and the NMR structure of the U6 snRNA stem–loop region. Our structure differs in many respects from both the NMR and X-ray structures of D5-Ai5γ in the bulge region. Electrostatic calculations and NMR chemical shift perturbation analyses reveal magnesium ion-binding sites in the tetraloop, internal bulge, and the AGC triad in the lower stem. Our results suggest that the structure, electrostatic environment, and the magnesium ion-binding sites within the tetraloop, bulge, and triad regions are conserved features of the splicing machinery of both the group II introns and the spliceosome that are likely key for catalytic function.